PENGARUH KOMPENSASI FINALSIAL DAN KOMPENSASI NON-FINANSIAL TERHADAP KINERJA KERJA KARYAWAN - Rahmiyanti, Sev; Wijaya, Mahatma (Jurnal Valuasi: Jurnal Ilmiah Ilmu Manajemen dan Kewirausahaan, 2025)
Human Resources (HR) are a very important asset for a company, because every business activity carried out requires HR to run it. Quality HR can be seen through high performance and productivity. Employee performance is related to the quality of behavior that focuses on tasks and work. One of the factors that influences employee performance is compensation, both financial and non-financial. Financial compensation generally includes salary, wages, incentives, and benefits. Meanwhile, non-financial compensation includes educational and training opportunities, work leave, work environment, transportation facilities, and promotions. This study uses a literature review method with a descriptive analysis approach. The research was conducted through a literature study, by reviewing literature books related to Compensation Management theory, as well as analyzing scientific articles, both reputable and non-reputable. The author selected 10 scientific articles related to financial compensation, non-financial compensation, and employee performance to be analyzed in depth. The selected articles have a publication period from 2019 to 2024. The purpose of writing this literature review is to explain the effect of financial and non-financial compensation on employee performance. Based on this study and previous studies, it can be concluded that financial and non-financial compensation have a joint effect on employee performance.